DAUN KLOROFIL SEBAGAI TERAPI ALAMI UNTUK MENGATASI MASALAH HIPERTENSI DI WILAYAH KERJA PUSKESMAS LAANG TANDUK KABUPATEN TORAJA UTARA - Musfirah, Musfirah; Syukur, Muhammad Syukur; Firdaus, Firdaus W Suhaeb; Sindi, Sindi Dea Lepong (Bina Generasi : Jurnal Kesehatan, 2024)
Hypertension is a silent killer because it rarely has clear symptoms. The purpose of this study was to determine the utilization of chlorophyll leaves as an alternative medicine to lower blood pressure in hypertension in the working area of the Laang Tanduk Health Center, North Toraja Regency.This study used a quantitative research design with a Cross Sectional and Qualitative Phenomenology approach or a combined method (Mix Methods). The research was conducted at the Laang Tanduk Health Center Work Area, North Toraja Regency. The sample size was 74 respondents, 1 key informant and 3 ordinary informants using questionnaires and in-depth interview guidelines.Based on the results of the researchers obtained, there is a relationship between knowledge and the incidence of hypertension with a value of p = 0.003 supported by the results of quantitative research stating that knowledge is very influential on the incidence of hypertension, there is a relationship between attitudes and the incidence of hypertension with a value of p = 0.003 supported by the results of qualitative research stating that processing has no relationship with the incidence of hypertension because processing is appropriate but still affected by hypertension.The conclusion of this study is that there is a relationship between knowledge, attitudes and the incidence of hypertension in the working area of the laang horn health center, there is no relationship between processing and the incidence of hypertension. The suggestion is that the knowledge, attitude and processing of chlorophyll leaves should be improved.